Serum iron and serum retinol level of severe acute malnourished children on therapeutic intervention with WHO/UNICEF recommended therapeutic food and home based therapeutic food - Bhandari, Bharti; Mehta, Anita (International Journal of Contemporary Pediatrics, 2021)
Background: The prevalence of anaemia and vitamin A deficiency among children with severe acute malnutrition (SAM) and their correction during nutritional rehabilitation are not well documented. This study assessed serum iron and serum retinol levels, effect of ready-to-use therapeutic foods (RUTF) and home based treatment on levels of serum iron and serum retinol level in SAM children. Methods: This was a simple randomised controlled trial in 6-59 months old children with SAM. Two groups of 70 each were divided, one was given RUTF and other home based food comparable to RUTF. Serum retinol and serum iron were measured on day 1 and 6 weeks of therapy. Results: Home based food was found better in terms of increase in serum iron than RUTF while there was no difference in rise of serum retinol in both the groups. There was no significant difference between day 1 value of serum iron in both the groups as p value was 0.82 but the level of serum iron at 6 weeks has shown significant difference in both the groups as p value was 0.0014 so there was significant increase in serum iron in group B in comparison to group A; the serum retinol value in both the groups has not shown any significant improvement. Conclusions: It was concluded home based food is better in correcting iron deficiency in SAM children as it is cheap, easily available, palatable, and acceptable than RUTF.